Biomass‐Derived Carbon Quantum Dot Sensitizers for Solid‐State Nanostructured Solar Cells. Issue 15 (20th February 2015) - Briscoe, Joe; Marinovic, Adam; Sevilla, Marta; Dunn, Steve; Titirici, Magdalena
Abstract New hybrid materials consisting of ZnO nanorods sensitized with three different biomass‐derived carbon quantum dots (CQDs) were synthesized, characterized, and used for the first time to build solid‐state nanostructured solar cells. The performance of the devices was dependent on the functional groups found on the CQDs. The highest efficiency was obtained using a layer‐by‐layer coating of two different types of CQDs.